Notfalls leben wir auch ohne Herz (Joseph Beuys) : Exemplarisches aus der Sammlung Speck. - Franzobel; Haller, Rudolf; Kelly, Robert; Kirkeby, Per; Klinger, Cornelia; Krug, Dietmar; Matt, Gerald; Merz, Mario; Noaek, Ruth; Rugoff, Ralph; Speck, Reiner; Steiner, Christian Theo; et al. (Wien : Kunsthalle Wien, 1997)
Andre, Carl ; Beuys, Joseph ; Broodthaers, Marcel ; Byars, James Lee ; Dahn, Walter ; Förg, Gunther ; Fulton, Hamish ; Herold, Georg ; Kiecol, Hubert ; Kirkeby, Per ; Kounellis, Jannis ; de Maria, Walter ; Merz, Mario ; Palermo, Blinky ; Pettibon, Raymond ; Polke, Sigmar ; Trockel, Rosemarie ; Twombly, Cy ; Weiner, Lawrence ; Speck, Reiner
Notfalls leben wir auch ohne Herz (Joseph Beuys) : Exemplarisches aus der Sammlung Speck, Kunsthalle Wien, 14.3. - 11.5.1997
Duits
kunstcatalogus